Experimental and Numerical Study on the Performance of Innovative Bifacial Photovoltaic Wall System. (October 2022) - Zhao, Oufan; Zhang, Wei; Chen, Mo; Xie, Lingzhi; Li, Jianhui; Li, Zihao; Zhong, Jianmei; Wu, Xin
Highlights: A BI-PVW system was innovatively developed, which could enhance the power generation. The maximum comprehensive utilization efficiency of solar energy could reach 40%. Ventilation of the BI-BVW system could bring 21.2% energy saving effect to the building. Abstract: The combination of PV and building envelope can provide clean energy for building and greatly reduce the occupancy area of PV. The challenges include how to increase the power generation and reduce the building energy consumption by using the PV system. In this study, bifacial PV module was innovatively combined with building exterior wall to form bifacial PV wall (BI-PVW) system, which could use the high reflectivity of wall to enhance the power generation of the back side and decrease the building heat load through indoor ventilation. To develop particular parameters of the best performance of the system, a preliminary design was carried out. And based on the design, an experimental platform was set up to analyze the energy utilization under different ventilation strategies. The comprehensive utilization efficiency of solar energy could reach 40% in sunny days. Then the simulation model validated by experiments was used to further analyze the performance of building with BI-PVW system. It could be found ventilation can bring 21.2% energy saving effect to the building. The results in this study could provide beneficial effect on the development of the application of bifacial PV in building.